Salafi dalam Kontestasi Islam di Pasuruan - Dewi Masita (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Pesantren with Ahlusunah wal pilgrims, both NU and Salafi, Shi'a, and Muhammadiyah in Pasuruan raises a problem how relatively new Salafi Islam can survive in the middle of the Islamic-dominated Pasuruan santri city affiliated with NU and Muhammadiyah. This research uses a sociological approach, namely understanding Islamic studies from a sociological perspective. The Islamic study in question is to discuss how the survival of Salafi groups in the Islamic contestation in Pasuruan. In understanding the aforementioned phenomena, researchers also use a phenomenological approach. The results showed that Salafists in the Contestation of Islam in Pasuruan turned out to be able to survive and show their existence in the fields of politics, economics, and education in the delivery of pure Islamic teachings, and returning to the al Qur’an, must obey the government as ulil amri. All Salafi appearances are attractively packaged (packaging). Salafi is not in politics but cooperates with the Pasuruan city government and the TNI, in aspect of Salafi education follows the state curriculum but still memorizes the Koran. In the economic aspect, if you do charity zakat and qurban or hajj and umrah, it must be by the sunnah.